FLOWER METAPHORS IN THE SCRIPTURES: - - Emmie Kussemiarti; Ontje Manurung; M. Imelda Kusumastuty (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
This research aims to identify which flowers are mentioned in the Scriptures and what the meanings are represented by the flowers (metaphors of the flowers). The data are gathered from the Scriptures itself and from other sources on the meanings/symbolism of flowers. They are analysed using the theories of semantics, metaphors, morphology, pragmatics, semiotics, and philosophy. The result shows that there are three kinds of flowers mentioned in the Scriptures, that is: Rose, Rose of Sharon,and Lily of the Valley.The rose symbolizes love, joy, and purity, the rose Sharon symbolizes humility and modesty, and Lily of the valley symbolizes hope and prosperity. Keywords: Flower Metaphor, Rose, Rose of Sharon, Lily of the Valley, Scriptures